Oligoclonal bands in multiple sclerosis: clinical-pathologic correlation. - Farrell, M; Kaufmann, J; Gilbert, J; Noseworthy, J; Armstrong, H; Ebers, G (1985)
Although oligoclonal banding is a characteristic feature of MS spinal fluid, some patients do not show this abnormality. Four of 18 consecutive patients with autopsy-proven MS had no oligoclonal bands (OB) in CSF during life or at postmortem. Patients with OB had numerous plasma cells in meninges and plaques (confirmed in sections stained for cytoplasmic immunoglobulin). The four patients without bands had few or no identifiable plasma cells. Therefore, lack of OB correlates with both inactivity of plaques and absence of plasma cells in plaques or meninges. This is another form of heterogeneity in MS.